+0

# 12 - 2x + 5 = -2 + (x-3)

0
31
1

12 - 2x + 5 = -2 + (x-3)

Guest Oct 29, 2017

#1
+5198
+1

12 - 2x + 5  =  -2 + (x - 3)

We don't need to keep the parenthesees since there is just addition outside them.

12 - 2x + 5  =  -2 + x - 3      Combine like terms on both sides.

17 - 2x  =  -5 + x             Add  5  to both sides of the equation.

5 + 17 - 2x  =  x              Add  2x  to both sides.

5 + 17  =  2x + x             Combine like terms again.

22  =  3x         Divide both sides by  3 .

$$\frac{22}{3}$$  =  x

hectictar  Oct 29, 2017
Sort:

#1
+5198
+1

12 - 2x + 5  =  -2 + (x - 3)

We don't need to keep the parenthesees since there is just addition outside them.

12 - 2x + 5  =  -2 + x - 3      Combine like terms on both sides.

17 - 2x  =  -5 + x             Add  5  to both sides of the equation.

5 + 17 - 2x  =  x              Add  2x  to both sides.

5 + 17  =  2x + x             Combine like terms again.

22  =  3x         Divide both sides by  3 .

$$\frac{22}{3}$$  =  x

hectictar  Oct 29, 2017

### 20 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details